Assessing the experience of using synthetic cannabinoids by means of interpretative phenomenological analysis. Issue 1 (December 2017) - Kassai, Szilvia; Pintér, Judit; Rácz, József; Böröndi, Brigitta; Tóth-Karikó, Tamás; Kerekes, Kitti; Gyarmathy, V.
Abstract Background New psychoactive substances (NPS) have been increasingly consumed by people who use drugs in recent years, which pose a new challenge for treatment services. One of the largest groups of NPS is synthetic cannabinoids (SCs), which are intended as a replacement to cannabis. While there is an increasing body of research on the motivation and the effects associated with SC use, little is known about the subjective interpretation of SC use by the people who use drugs themselves. The aim of this study was to examine the experiences and personal interpretations of SC use of users who were heavily dependent on SC and are in treatment. Methods A qualitative research method was applied in order to explore unknown and personal aspects of SC use. Semi-structured interviews were conducted with six participants who had problematic SC use and entered treatment. The research was conducted in Hungary in 2015. We analyzed data using interpretative phenomenological analysis (IPA). Results Participants perceived SCs to be unpredictable: their initial positive experiences quickly turned negative. They also reported that SCs took over their lives both interpersonally and intrapersonally: the drug took their old friends away, and while initially it gave them new ones, in the end it not only made them asocial but the drug became their only friend, it hijacked their personalities and made them addicted. Conclusions Participants experienced rapid development of effects and they had difficulties interpreting or integrating these experiences. The rapid alteration of effects and experiences may explain the severe psychopathological symptoms, which may be important information for harm reduction and treatment services. Since, these experiences are mostly unknown and unpredictable for people who use SCs, a forum where they could share their experiences could have a harm reducing role. For a harm reduction point of view of SCs, which are underrepresented in literature, it is important to emphasize the impossibility of knowing the quantity, purity, or even the number of different SC compounds in a particular SC product. Our study findings suggest that despite the adverse effects, including a rapid turn of experiences to negative, rapid development of addiction and withdrawal symptoms of SCs, participants continued using the drug because this drug was mostly available and cheap. Therefore, a harm reduction approach would be to make available and legal certain drugs that have less adverse effects and could cause less serious dependence and withdrawal symptoms, with controlled production and distribution (similarly to cannabis legalization in the Netherlands).